THE EFFECT OF OWNERSHIP STRUCTURE ON EARNINGS MANAGEMENT : MODERATION AND MEDIATION MODELS - Nur Afifah; Suwarno Suwarno (LPPM STIE Muhammadiah Bandung, 2026)
This study examines the influence of ownership structures on earnings management practices among manufacturing firms listed on the Indonesia Stock Exchange (IDX) during 2021–2024. It further investigates whether board composition heterogeneity moderates this relationship and whether firm performance mediates it. A quantitative design was employed, utilizing audited financial statements and annual corporate reports as secondary data. From purposive sampling, 100 firm-level observations were analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM) with SmartPLS. The findings indicate that concentrated ownership, managerial shareholding, foreign equity participation, and institutional investment do not significantly affect earnings management behaviour. Likewise, diversity in board membership does not alter the ownership–earnings management nexus. In contrast, firm performance shows a significant positive association with earnings management, though it does not operate as a mediating mechanism. Interpreted through agency theory, the results suggest that prevailing ownership configurations and board oversight remain insufficient to mitigate opportunistic managerial conduct, particularly under performance pressures. These insights contribute to ongoing debates on corporate governance and reporting credibility, offering implications for investors, regulators, and decision-makers. However, the conclusions are constrained by the study’s sectoral focus and limited temporal scope, which restricts broader generalization.